Pelatihan dan Pemanfaatan Penyimpanan Arsip Digital dengan Teknologi Cloud Google Drive pada Mitra Kader PKK Kelurahan Ragunan Jakarta Selatan - Eko Setia Budi; Eva Zuraidah; Ipin Sugiyarto; Besus Maula Sulthon; Herliansyah Herliansyah; Istiana Wahidah; Retno Widianingsih; Putra Ariyanto; Alby Sukmana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
PKK Cadres, Ragunan Subdistrict, South Jakarta, social organization as a forum and means of development for every member of the community who grows and develops on the basis of awareness and social responsibility from and for the community, especially the younger generation in the region, especially engaged in social welfare businesses. Difficulty accessing information & technology as well as other sources of information. Limited understanding of managing and processing large or big data in optimizing the Ragunan Village, South Jakarta. There are several obstacles related to their activities, one of which is related to storing images, and other files to create then catalogs and social activities which can later be distributed and used anytime and anywhere, one of the technologies that can be used for storage is using cloud technology from Google, namely google drive, by utilizing and using this technology PKK Cadres can store data and social activities anytime and anywhere.